Bifunctional Phosphonium Salt‐catalyzed Enantioselective [4+2] Annulation of Isoindigos with Allenes: Access to Complex Heterocycles with Centerpiece of 4H‐Pyrans. Issue 12 (17th April 2020) - Du, Juan; Wu, Jia‐Hong; Zhu, Lixiang; Ren, Xiaoyu; Jiang, Chunhui; Wang, Tianli
Abstract: Structurally fused heterocycles encompassing 4 H ‐pyran centerpiece are prevalent scaffolds with promising biological activities, but have daunting synthetic challenges. Herein, we presented a regio‐ and stereoselective [4+2] annulation of isoindigo derivatives with allenes by bifunctional phosphonium catalysis. This protocol provides a complementary way for accessing complex heterocyclic compounds. Abstract :